Prospects for improving legislative regulation of electricity quality requirements in Ukraine and the EU - R.I. Hrytsak; V.S. Tsykh (Технічна інженерія)
The issue of electricity quality is extremely important today. Its level affects the correct and uninterrupted operation of electrical appliances, the level of losses in power grids, energy efficiency of enterprises and safety for others. Continuous improvement of power quality indicators (PQI) and study of factors that deteriorate them allows us to maintain the required level of quality at least in the time of rapid development of semiconductor (nonlinear) systems.